Security system with RFID control using E-KTP and internet of things - Andi Ainun Najib; Rendy Munadi; Nyoman Bogi Aditya Karna (Institute of Advanced Engineering and Science, 2021)
Crimes against property without using violence, in this case, are theft and burglary is the type of crime that is most common every year. However, home security needs a security system that is more efficient and practical. To overcome this, an internet of things (IoT) is needed. This research evaluated the performance prototype by reading distance from the radio frequency identification (RFID) reader using E-KTP and quality of service performance (i.e throughput and delay) from application android. This research design smart door lock using RFID sensor, passive infrared sensor (PIR), solenoid as door locks, buzzer, led, E-KTP as RFID tags and also android application to controlling and monitoring made with android studio is connected to NodeMCU V3 ESP8266 as storage data and connect with firebase realtime database instead of conventional keys. This research focuses on performance prototype and quality of service from features application is work well. Related to previous works, our evaluation shows that the performance prototype can read identity card (E-KTP) with a maximum distance is 4 cm, and performance quality of service for an application show that throughput and delay with a perfect index according to standardization telecommunications and internet protocol harmonization over network (TIPHON) depending on what features are being evaluated.